Influence of Natural American Spirit advertising on current and former smokers' perceptions and intentions. Issue 5 (21st October 2017) - Gratale, Stefanie K; Maloney, Erin K; Sangalang, Angeline; Cappella, Joseph N
Abstract : Objective: This study sought to demonstrate causal effects of exposure to Natural American Spirit (NAS) advertising content on misinformed beliefs of current and former smokers, and to empirically establish these beliefs as a mechanism driving intentions to use NAS. Methods: Our study employed a randomised experimental design with 1128 adult daily, intermittent and former smokers. We compared participants who were exposed to NAS advertisements or claims made in the advertisements with those in a no-message control group to test the effects of NAS advertising content on inaccurate beliefs about NAS and attitudes and intentions towards the product. Results: One-way analysis of variance revealed that exposure to NAS advertisements produced inaccurate beliefs about the composition of NAS cigarettes among current and former smokers (p<0.05). Planned contrasts indicated a compilation of arguments taken directly from NAS advertisements resulted in significantly greater beliefs that NAS cigarettes are healthier/safer than other cigarettes (for former smokers, t(472)=3.63, p<0.001; for current smokers, t(644)=2.86, p=0.004), demonstrating that suggestive claims used in the brand's marketing have effects on beliefs not directly addressed in the advertisements. Regression and mediation analyses showed that health-related beliefs predict attitudes towards NAS for current and former smokers, and mediate intentions to use NAS. Conclusions: The findings of this study provide causal support for the need for further regulatory action to address the potentially harmful ramifications of claims used in NAS advertising.